Searching for resistance genes in bacteria of clinical origin, commonly found in urinary tract infections (Research, Society and Development, 2022)
Urinary Tract Infections (UTI) are one of the most common infectious diseases diagnosed. Intensive Care Units (ICU) are responsible for a large proportion of antibacterial drug consumption and have major socioeconomic impacts. Since most treatments start or are done completely empirically, knowledge of the organisms, their epidemiological characteristics and their antibacterial susceptibility that may vary over time is mandatory. Therefore this work becomes of great relevance, since it intends through this review to demonstrate the need to sequence bacteria, comparing them and evaluating the resistance gene. We used all publications that had data on resistance gene research in bacteria of clinical origin commonly found in urinary tract infections, commonly found in urinary tract infections, official scientific publications of the World Health Organization (WHO) and governmental, within the given date (2019-2021). Data were collected using scientific databases: LILACS, PUBMED, PERIODICOS CAPES, SCIENCE DIRECT, BVS, SCIELO, COCHRANE LIBRARY, HIGHWIRE PRESS, SCOPUS and ELSEVIER. A total of 14 articles (Table 1) were found in the databases. The descriptors used were: urinary tract, gene search, resistance in bacteria, urinary infection, in English, Portuguese and Spanish. We obtained the articles described below in Table 1 and discussed them in the form of topics related to the theme.